Differential Social Performance of Religiously-Affiliated Microfinance Institutions (MFIs) in Base of Pyramid (BoP) Markets - Casselman, R. Mitch (Journal of business ethics, 2015)
As the debate over the value of microfinance institutions (MFIs) intensifies, it remains apparent that microfinance may, at the very least, be considered as one tool in the arsenal of the war against poverty in base of pyramid (BoP) markets. Given the variety of actors in the microfinance arena, stakeholders have placed a relatively new emphasis on performance reporting for MFIs, allowing comparisons and identifications of performance gaps. One result of this scrutiny is an increased importance placed on MFIs’ social performance, with an eye to understanding measures of MFIs’ intent, process, and results in the social realm—in addition to their financial sustainability. While a number of factors may explain differences in social performance, in this paper we take a close look at a particular factor that may have a positive relationship with social performance—that of an MFI’s religious affiliation or religiosity. Using archival data, we derived three sets of randomly paired samples, pairing religious MFIs with non-religious ones, and compared social performance indicators derived from the literature across the samples. We sought to understand whether religiously-affiliated MFIs would, in fact, demonstrate stronger social performance intent, wider social performance reach via service delivery processes, and better social performance outcomes in BoP markets. Statistical analysis provided preliminary evidence that religiously-affiliated MFIs display stronger social performance, suggesting new avenues for future research.